2019
DOI: 10.20867/tosee.05.11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Seasonality Impact on the Business Performance of Global Chain Hotels

Abstract: Starting with the notion that seasonality is one of the greatest challenges for the most hotels and tourist destinations, and without an exception for the hotels in European Mediterranean destination, this paper aims to gain knowledge of the coherence between business performance of global chain hotels and degree of seasonality, and if business or leisure hotels are more successful from the aspect of seasonality degree. Business performance is approximated by the following indicators: accommodation occupancy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Some researchers have also focussed on assessing the economic effects of the seasonality of the tourism industry from the perspective of tourism service providers. Vrkljan et al (2019) have found that tourism seasonality is positively correlated with business performance, which could be improved only by reducing its effects. Some researchers (Grizane, 2016;Corluka, 2019;Chung, 2009;Koenig and Bischoff, 2004;Mart ın Mart ın et al, 2020;Szivas et al, 2003;BarOn, 1975) have assessed the economic effects of seasonality by means of such criteria as the price of tourism service, amount of revenue earned, investment, exploitation efficiency of resources and infrastructure and development of the territory.…”
Section: Effects Of Tourism Seasonalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have also focussed on assessing the economic effects of the seasonality of the tourism industry from the perspective of tourism service providers. Vrkljan et al (2019) have found that tourism seasonality is positively correlated with business performance, which could be improved only by reducing its effects. Some researchers (Grizane, 2016;Corluka, 2019;Chung, 2009;Koenig and Bischoff, 2004;Mart ın Mart ın et al, 2020;Szivas et al, 2003;BarOn, 1975) have assessed the economic effects of seasonality by means of such criteria as the price of tourism service, amount of revenue earned, investment, exploitation efficiency of resources and infrastructure and development of the territory.…”
Section: Effects Of Tourism Seasonalitymentioning
confidence: 99%
“…Some researchers have also focussed on assessing the economic effects of the seasonality of the tourism industry from the perspective of tourism service providers. Vrkljan et al. (2019) have found that tourism seasonality is positively correlated with business performance, which could be improved only by reducing its effects.…”
Section: Effects Of Tourism Seasonalitymentioning
confidence: 99%
“…An even more important issue concerns the instability of the number of hotel staff required throughout the year, leading to variations in the demand for local employment in the tourism sector. The seasonal variation in the tourism sector also has an indirect impact on the distribution chain, transportation, and local commerce of products (Bar-On, 1999;Vrkljan et al, 2019). This means that the tourism sector seasonality poses a problem vis-à-vis employment stability, sustainable development, and economic growth (United Nations Sustainable Development Goal 8: sustainable tourism is one of the subtopics).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tourism seasonality in Portugal has not been thoroughly studied in terms of space, distribution of clients, quality of service offered, revenue, although some authors have studied the seasonality in Portugal or Mediterranean destinations, such as Duro (2016), Mitra (2020), Vrkljan et al (2019), Neves et al (2008), Gouveia (2014) andVergori (2017). Some of these studies have some limitations as far as the implications of the scope or method used are concerned (Gouveia, 2014;Vergori, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%